Pengaruh Insentif Pajak, Financial Distress, dan Capital Intensity Terhadap Konservatisme Akuntansi - Hari Stiawan; Fitria Eka Ningsih; Suciati Nurani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Companies that carry out conservatism in financial statements there are various factors, researchers suggest these factors, there are tax incentives, financial distress, and capital intensity. Research objectives are find out whether tax incentives, financial distress and capital intensity have an effect on accounting conservatism. Based on Sugiyono (2017:2), the research method is a scientific way to obtain data with certain goals and uses. Based on those research method, there are five keywords that need to be considered, scientific method, data, objectives, and uses. The type of research used by this research is quantitative research. This research was conducted by 14 food and beverage companies. In this study using secondary data. Based on the results of research, tax incentives and financial distress have a negative effect on accounting conservatism. Meanwhile, capital intensity does not affect accounting conservatism. Based on the conclusions and limitations of the research, some suggestions can provide positive benefits for increasing the research sample by using all types of companies listed on the Indonesia Stock Exchange so that they are not limited to food and beverage sub-sector companies